IMPLEMENTASI PASAL 12 AYAT 1 POINT (a) UNDANG-UNDANG PENDIDIKAN NASIONAL NOMOR 20 TAHUN 2003 DI SMP XAVERIUS 1 PALEMBANG - Ishak Shafar (Conciencia, 2017)
12 paragraph 1 point (a) National education system law number 20 of 2003 at Xaverius 1 Middle School in Palembang. 12 paragraph 1 point (a) National education law number 20 of 2003 at Xaverius 1 Middle School in Palembang. 12 paragraph 1 point (a) National education law number 20 of 2003 (Every student in each education unit has the right to receive religious education in accordance with the religion he adheres to and is supported by religious educators) in SMP Xaverius 1 Palembang has never been implemented. Religious education carried out in the classroom is only Catholic education for all students with diverse religions (Of the 970 students; 218 Catholics, 112 Muslims, 395 Buddhists, 241 Protestants, and 4 Hindus person). The implementation of religious education like this besides not according to the mandate of the Law, will further have a negative impact on the development of children's education, parents of students, and including national education in general. Negative impacts for students; Students are guaranteed not to receive religious education material according to their religion and even given religious education material that is not in accordance with the religion of the students, so that students do not understand their religion, carry out teaching plus material given by other religions.